2017
DOI: 10.1016/j.jim.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Free light chains: Eclectic multipurpose biomarker

Abstract: The production of antibodies is accompanied by a slight excess of synthesis of κ and λ immunoglobulin light chains; small amounts of them are released in the peripheral blood and can also be found in various body fluids, such as synovial fluid, cerebrospinal fluid, urine and saliva. They are rapidly filtered by the glomerulus and >99% are reabsorbed from the cells of the proximal convoluted tubule, making them present in the urine in only trace amounts. The production of an excess of protein without a reason o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 105 publications
(122 reference statements)
2
49
0
1
Order By: Relevance
“…Two important processes in heart failure are inflammation and renal impairment, both of which can increase serum immunoglobulin free light chain (FLC) κ and λ concentrations. The sum of circulating FLC κ and λ is increased in patients with autoimmune diseases 202 and DCM (A.Mat., unpublished results). A communitybased study of 15,000 individuals of the general population showed that high FLC concentration was associated with an increased risk of all-cause mortality 203 .…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…Two important processes in heart failure are inflammation and renal impairment, both of which can increase serum immunoglobulin free light chain (FLC) κ and λ concentrations. The sum of circulating FLC κ and λ is increased in patients with autoimmune diseases 202 and DCM (A.Mat., unpublished results). A communitybased study of 15,000 individuals of the general population showed that high FLC concentration was associated with an increased risk of all-cause mortality 203 .…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…However, currently the biological functions of LCs are being recognized. Due to their involvement in pathogenesis of various diseases, LCs are now considered as possible diagnostic markers [ 1 , 2 , 3 ]. Further, LCs play an important role in activation of mast cells and neutrophils, as well as in humoral immunity by supporting the antigen binding with sufficient affinity by specific antibodies [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their involvement in pathogenesis of various diseases, LCs are now considered as possible diagnostic markers [ 1 , 2 , 3 ]. Further, LCs play an important role in activation of mast cells and neutrophils, as well as in humoral immunity by supporting the antigen binding with sufficient affinity by specific antibodies [ 1 ]. This is often associated with the development of various chronic inflammatory disorders and tumor-related inflammation, in which LCs seem to promote the pathological immune reactivity of particular cells [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, FLCs have become an attractive novel target, with the aim of using antagonists to reduce inflammation and disease activity. This concept remains relatively unexplored, and further prospective studies are needed to validate the use of FLCs as a biomarker in different disease cohorts .…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin‐free light chains (FLCs) κ and λ are produced by plasma cells in slight excess for the need of immune response and are therefore assayable in peripheral blood, as in other biological fluids, such as urine, saliva, cerebrospinal fluid, and synovial fluid . However, recently, different biological functions have been attributed to these molecules, suggesting that they are not just a secondary product of immunoglobulin synthesis.…”
Section: Introductionmentioning
confidence: 99%